Volunteer motivators for participating in HIV vaccine clinical trials in Nairobi, Kenya. - Borna A Nyaoke (PLoS ONE, 2017)
1.5 million Kenyans are living with HIV/AIDS as per 2015 estimates. Though there is a notable decline in new HIV infections, continued effort is still needed to develop an efficacious, accessible and affordable HIV vaccine. HIV vaccine clinical trials bear risks, hence a need to understand volunteer motivators for enrolment, retention and follow-up. Understanding the factors that motivate volunteers to participate in a clinical trial can help to strategize, refine targeting and thus increase enrolment of volunteers in future HIV vaccine clinical trials. The health belief model classifies motivators into social benefits such as 'advancing research' and collaboration with science, and personal benefits such as health benefits and financial interests.A thematic analysis was carried out on data obtained from four HIV clinical trials conducted at KAVI-Institute of Clinical Research in Nairobi Kenya from 2009 to 2015. Responses were obtained from a Questionnaire administered to the volunteers during their screening visit at the research site.Of the 281 healthy, HIV-uninfected volunteers participating in this study; 38% were motivated by personal benefits including, 31% motivated by health benefits and 7% motivated by possible financial gains. In addition, 62% of the volunteers were motivated by social benefits with 20% of who were seeking to help their family/society/world while 42% were interested in advancing research.The majority of volunteers in the HIV vaccine trials at our site were motivated by social benefits, suggesting that altruism can be a major contributor to participation in HIV vaccine studies. Personal benefits were a secondary motivator for the volunteers. The motivators to volunteer in HIV clinical trials were similar across ages, education level and gender. Education on what is needed (including volunteer participation) to develop an efficacious vaccine could be the key to greater volunteer motivation to participate in HIV vaccine clinical trials.